Sargassum seaweed health menace in the Caribbean: clinical characteristics of a population exposed to hydrogen sulfide during the 2018 massive stranding. (4th March 2021) - Resiere, Dabor; Mehdaoui, Hossein; Florentin, Jonathan; Gueye, Papa; Lebrun, Thierry; Blateau, Alain; Viguier, Jerome; Valentino, Ruddy; Brouste, Yannick; Kallel, Hatem; Megarbane, Bruno; Cabie, André; et al.
Abstract: Background: Since 2011, there have been ongoing massive unexplained increases of sargassum seaweed strandings along the coastlines of Caribbean countries. The objective of our study was to describe the clinical characteristics of patients exposed to noxious emissions of decomposing sargassum seaweed. Methods: This observational study included patients from January 2018 to December 2018 for complaints attributed to decomposing sargassum seaweed. History and geographical characteristics of sargassum seaweed strandings as well as detection of ambient air hydrogen sulfide (H2 S) levels were documented during the inclusion period. Findings: A total of 154 patients were included. Mean exposure period was 3 months. Neurological (80%), digestive (77%) and respiratory (69%) disorders were the most frequent reasons for medical visit. Temporal distribution of medical visits was related to history of strandings. Geographical origins of patients were consistent with the most impacted areas of strandings as well as the most elevated ambient air H2 S levels. Interpretation: The toxicological syndrome induced by sargassum seaweed exposure is close to the toxidrome associated with acute H2 S exposure in the range of 0–10 ppm. Our study suggests that patients living in massive stranding areas may be exposed to H2 S > 5 ppm for 50 days per year.